miR-212 and miR-132 Are Downregulated in Neurally Derived Plasma Exosomes of Alzheimer’s Patients - Cha, Diana J.; Mengel, David; Mustapic, Maja; Liu, Wen; Selkoe, Dennis J.; Kapogiannis, Dimitrios; Galasko, Douglas; Rissman, Robert A.; Bennett, David A.; Walsh, Dominic M. (Frontiers in Neuroscience, 2019)
Recently it was discovered that brain cells release extracellular vesicles (EV) that can pass from brain into blood. These findings raise the possibility that brain-derived EV’s present in blood can be used to monitor disease processes occurring in the central nervous system. Since the levels of certain micro-RNAs (miRNAs) have been reported to be altered in Alzheimer’s disease (AD) brain, we sought to assess miRNA dysregulation in AD brain tissue and to determine if these changes were reflected in neural EVs isolated from blood of subjects with AD. To this end, we employed high-content miRNA arrays to search for differences in miRNAs in RNA pools from brain tissue of AD (n=5), high pathological control (HPC) (n=5), or cognitively intact pathology-free controls (n=5). Twelve miRNAs were altered by >1.5-fold in AD compared to controls, and six of these were also changed compared to HPCs. Analysis of hits in brain extracts from 11 AD, 7 HPCs and 9 controls revealed a similar fold difference in these six miRNAs, with three showing statistically significant group differences and one with a strong trend towards group differences. Thereafter, we focused on the four miRNAs that showed group differences and measured their content in neurally-derived blood EVs isolated from 64 subjects: 16 patients with early stage dementia and a CSF Aβ42 + tau profile consistent with AD, 16 individuals with mild cognitive impairment (MCI) and an AD CSF profile, and 31 cognitively intact controls with normal CSF Aβ42 + tau levels. ROC analysis indicated that measurement of miR-132-3p in neurally-derived plasma EVs showed good sensitivity and specificity to diagnose AD, but did not effectively separate individuals with AD-MCI from controls. Moreover, when we measured the levels of a related miRNA, miR-212, we found that this miRNA was also decreased in neural EVs from AD patients compared to controls. Our results suggest that measurement of miR-132 and miR-212 in neural EVs should be further investigated as a diagnostic aid for AD and as a potential theragnostic.